Self-association of the erythroid transcription factor GATA-1 mediated by its zinc finger domains. - Crossley, M (1995)
GATA-1, the founding member of a distinctive family of transcription factors, is expressed predominantly in erythroid cells and participates in the expression of numerous erythroid cell-expressed genes. GATA-binding sites are found in the promoters and enhancers of globin and nonglobin erythroid genes as well as in the alpha- and beta-globin locus control regions. To elucidate how GATA-1 may function in a variety of regulatory contexts, we have examined its protein-protein interactions. Here we show that GATA-1 self-associates in solution and in whole-cell extracts and that the zinc finger region of the molecule is sufficient to mediate this interaction. This physical interaction can influence transcription, as GATA-1 self-association is able to recruit a transcriptionally active but DNA-binding-defective derivative of GATA-1 to promoter-bound GATA-1 and result in superactivation. Through in vitro studies with bacterially expressed glutathione S-transferase fusion proteins, we have localized the minimal domain required for GATA-1 self-association to 40 amino acid residues within the C-terminal zinc finger region. Finally, we have detected physical interaction of GATA-1 with other GATA family members (GATA-2 and GATA-3) also mediated through the zinc finger domain. These findings have broad implications for the involvement of GATA factors in transcriptional control. In particular, the interaction of GATA-1 with itself and with other transcription factors may facilitate its function at diverse promoters in erythroid cells and also serve to bring together, or stabilize, loops between distant regulatory elements, such as the globin locus control regions and downstream globin promoters. We suggest that the zinc finger region of GATA-1, and related proteins, is multifunctional and mediates not only DNA binding but also important protein-protein interactions.